Sobre a percepção: um processo objetivo, categórico e não conceitual - Oliveira, Debora Fontoura de (Universidade do Vale do Rio dos Sinos, 2015)
This work aims to present and evaluate different theories regarding the perceptual process, defending that the perception is an objective, categorical and non-conceptual process. The idea is to, along with Tyler Burge’s position, ensure that the perception is a representational process where the perceptual experience consists in the direct apprehension of sensory data, which are used as the basis for the construction of perceptual representations. The perceptual representations are designed as proxytypes, and they serve as the non-conceptual content of the perception and correspond to the outside world. They represent the objects and the states of affairs of the world due to a similarity between the properties of the objects and the sensory properties represented by the individuals. The objects and their properties are then represented through the integration of sensory information by the mechanism of categorical perception, which is responsible for the discrimination and identification of that information in perceptual categories, and are independent of conceptual structures. This way, we propose that the perception is objective for two reasons (a) because it is a process that assumes as true a realism of the physical world and allows us to access and understand the objects arranged in the world in an objective way, and (b) because it is a process that is accomplished by both human and non-human animals. Perception is a categorical process because it admits that sensory information is categorized into perceptual representations during the actual perceptual experience, and this function is performed by categorical perception. At the same time, it is not conceptual, since any creature equipped with a sensory and nervous system is able to perceive the world even if it does not have a concept for describing given contents or not yet has the ability to refer to them demonstratively.
Keywords: Anti-individualismo perceptual; Não conceitualismo perceptual; Percepção; Percepção categórica; Proxytypes; Perceptual anti-individualism; Perceptual non-conceptualism; Perception; Categorical perception; ACCNPQ::Ciências Humanas::Filosofia